Priming with MF59 adjuvanted versus nonadjuvanted seasonal influenza vaccines in children – A systematic review and a meta-analysis. Issue 3 (16th January 2020) - Patel, Manish M.; Davis, William; Beacham, Lauren; Spencer, Sarah; Campbell, Angela P.; Lafond, Kathryn; Rolfes, Melissa; Levine, Min Z.; Azziz-Baumgartner, Eduardo; Thompson, Mark G.; Fry, Alicia M.
Highlights: Titers against A and B influenza viruses after aIIV vs. IIV were 2–3 fold higher in children <5 years. One aIIV dose had a similar response to two IIV doses against Type A influenza viruses. Antibody response to aIIV was highest among children 6–35 months. Adjuvanted seasonal influenza vaccines may improve priming of immune systems in children. Abstract: Background: Identifying optimal priming strategies for children <2 years could substantially improve the public health benefits of influenza vaccines. Adjuvanted seasonal influenza vaccines were designed to promote a better immune response among young vaccine-naïve children. Methods: We systematically reviewed randomized trials to assess hemagglutination inhibition (HAI) antibody response to MF59-adjuvanted inactivated influenza vaccine (aIIV) versus nonadjuvanted IIV among children. We estimated pooled ratios of post-vaccination HAI geometric mean titer (GMT) for aIIV versus IIV and confidence intervals (CIs) using the pooled variances derived from reported CIs. Results: Mean age was 28 months (range, 6–72 months). Children received vaccines with either 7.5 μg (6–35 months) or 15 μg (≥36 months) hemagglutinin of each strain depending on age. Seven of eight trials administered trivalent vaccines and one used quadrivalent vaccine. Pooled post-vaccination GMT ratios against the three influenza vaccine strains were 2.5–3.5 fold higher after 2-dose-aIIV versus 2-dose-IIV among children 6–72 months, and point estimates were higher among children 6–35 months compared with older children. When comparing 1-dose-aIIV to 2-dose-IIV doses, pooled GMT ratios were not significantly different against A/H1N1 (1.0; 95% CI: 0.5–1.8; p = 0.90) and A/H3N2 viruses (1.0; 95% CI: 0.7–1.5; p = 0.81) and were significantly lower against B viruses (0.6; 95% CI: 0.4–0.8; p < 0.001) for both age groups. Notably, GMT ratios for vaccine-mismatched heterologous viruses after 2-dose-aIIV compared with 2-dose-IIV were higher against A/H1N1 (2.0; 95% CI: 1.1–3.4), A/H3N2 (2.9; 95% CI: 1.9–4.2), and B-lineage viruses (2.1; 95% CI: 1.8–2.6). Conclusions: Two doses of adjuvanted IIV consistently induced better humoral immune responses against Type A and B influenza viruses compared with nonadjuvanted IIVs in young children, particularly among those 6–35 months. One adjuvanted IIV dose had a similar response to two nonadjuvanted IIV doses against Type A influenza viruses. Longer-term benefits from imprinting and cell-mediated immunity, including trials of clinical efficacy, are gaps that warrant investigation.